Problem solving technique based on trisilas culture to improve self- regulated learning (SRL) for students in the digital era - Komara, Indra Bangkit; Hartanto, Dody; Barida, Muya; Santosa, Hardi; Saputra, Wahyu Nanda Eka (Universitas Islam Negeri Raden Intan Lampung, 2024)
Easy internet access is an opportunity for students to obtain various information. Fast digital information that is not balanced with Self-Regulated Learning (SRL) is a serious problem for students. This research aims to determine the effectiveness of problem solving techniques based on Trisilas culture to improve SRL in students. Trisilas is a Sundanese cultural philosophy that is used as a value in social life. The technique problem solving based on trisilas culture consisting of silih asah, silih asih, silih asuh in learning. The method used in this research is a quantitative experiment by examining whether there is an effect of group guidance on problem solving techniques based on trisilas culture on students' SRL. The experimental design used was a non-equivalent control-group design. The instrument in this research used a Scale of Self-Regulated Learning (SSRL). The results of the research showed that after the intervention of group guidance on problem solving techniques based on Trisilas culture, there was an increase of 16.75% in the level of SRL in students. According to the results of the independent sample t test, there is a difference in SRL after or before the intervention, with a 2-tailed significance value of 0.002 <0.05. Currently, there are not many studies that utilize problem- solving techniques based on Trisilas culture in guidance and counseling. The conclusion of this research is that Trisilas culture is a new alternative solution in improving SRL and shows that group guidance on problem solving techniques based on Trisilas culture is effective in making a significant contribution to increasing SRL in students in the digital era.